Heavy drinking in adolescents is associated with change in brainstem microstructure and reward sensitivity. (21st July 2019) - Galinowski, André; Miranda, Ruben; Lemaitre, Hervé; Artiges, Eric; Paillère Martinot, Marie‐Laure; Filippi, Irina; Penttilä, Jani; Grimmer, Yvonne; van Noort, Betteke M.; Stringaris, Argyris; Becker, Andreas; Isensee, Corinna; et al.
Abstract : Heavy drinker adolescents: altered brainstem microstructure. Abstract: The cortical‐cerebellar circuit is vulnerable to heavy drinking (HD) in adults. We hypothesized early microstructural modifications of the pons/midbrain region, containing core structures of the reward system, in HD adolescents. Thirty‐two otherwise symptom‐free HDs at age 14 (HD14) and 24 abstainers becoming HDs at age 16 (HD16) were identified in the community with the Alcohol Use Disorders Identification Test (AUDIT) and compared with abstainers. The monetary incentive delay (MID) task assessed reward‐sensitive performance. Voxelwise statistics of diffusion tensor imaging (DTI) values in the thalamo‐ponto‐mesencephalic region were obtained using tract‐based spatial statistics. Projections between the ventral tegmental area (VTA) and the nucleus accumbens (NAcc) were identified by probabilistic tractography. Lower fraction of anisotropy and higher radial diffusivity (RD) values were detected in the upper dorsal pons of HD14 adolescents, and a trend for higher RD in HD16, compared with abstainers. When expecting reward, HD14 had higher MID task success scores than abstainers, and success scores were higher with a lower number of tracts in all adolescents. In symptom‐free community adolescents, a region of lower white matter (WM) integrity in the pons at age 14 was associated with current HD and predicted HD at age 16. HD was related to reward sensitivity.